Essentials of meteorology an invitation to the atmosphere (Mindtap Course List) - Ahrens, C. Donald; Henson, Robert (Cengage Learning, 2017)
Essentials of meteorology, 8th Edition, is written for students interested in gaining insights into the dynamic workings of the atmosphere. The authors' ability to explain relatively complicated ideas in an easy-to-understand way lets both science and nonscience majors visualize the principles of meteorology. Online animations help you to immediately apply the text material and understand the underlying meteorological principles, and appendices allow you to explore meteorological data such as world temperature extremes and precipitation extremes over a 30-year period.
Keywords: Meteorologie; Einführung -- 2017